Assessing the Risk of Fraudulent Financial Reporting in Indonesian Banking Companies Through the Lens of Hexagon Fraud Analysis - Sare, Mathildis Tellyani Sega; Kurniawati, Anggreni Dian (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
The study aims to determine the impact of hexagon fraud on the detection of potential fraudulent financial statements. The study identified several factors that may have contributed to the emergence of potentially fraudulent financial reporting. These factors included the financial stability of the pressure element, the ineffective monitoring of the opportunity element, the change of auditor of the rationalization element, changes in the director of the capability element, the CEO duality of the ego element, and the political connection of the collusion element. The Eckel Index projects the possibility of fraudulent financial statements. The sample in this study is a banking company listed on the Indonesian Stock Exchange in the period 2018 to 2022. Sample obtained by purposive sampling. This study will highlight the possibility of fraudulent financial reporting, particularly regarding income smoothing practices used by Indonesian banks. The insights obtained from the hexagon fraud analysis can be leveraged by a banking institution to enhance its sustainable management procedures in the future.